A logical development: biomedicine's fingerprints are on the instrument of close reading in Charonian Narrative Medicine. Issue 3 (27th January 2022) - Neilson, Shane
Abstract : Narrative Medicine as originated by Rita Charon began as an attempt to redress the unopposed biomedicalisation of the medical profession. Although the movement has been self-positioned as a corrective to deliver an ideal of care, it began within the rhetorical framework of biomedicine and not outside of it. Thus, Narrative Medicine justifies itself in biomedical terms, invoking instrumental rationales for its use. This seeming 'scientification' of narrative is only half of the biomedicine-indebted Narrative Medicine story. An equally important but as-yet unmentioned debt is the quasi-scientific origin story of Narrative Medicine's signature method of close reading. Thus, there is an inherent paradox at the heart of the Narrative Medicine movement: designed to resist a reductive biomedicine, it exists in a dependent relationship on biomedicine at the level of justification and at the level of praxis. Thus, it is an open question if the Narrative Medicine movement is the proper vehicle for a rebalancing of humanities and biomedicine.